High-Resolution Magnetic Resonance Colonography and Dynamic Contrast-Enhanced Magnetic Resonance Imaging in a Murine Model of Colitis - Mustafi, Devkumar (2010)
Inflammatory bowel disease, including ulcerative colitis, is characterized by persistent or recurrent inflammation and can progress to colon cancer. Colitis is difficult to detect and monitor noninvasively. The goal of this work was to develop a preclinical imaging method for evaluating colitis. Herein, we report improved MRI methods for detecting and characterizing colitis noninvasively in mice, using high-resolution in vivo MR images and dynamic contrast-enhanced MRI studies, which were confirmed by histologic studies in a murine model of colitis. C57Bl6/J male mice were treated with 2.5% dextran sulfate sodium in their drinking water for 5 days to induce colitis. MR images were acquired using a 9.4-T Bruker scanner from 5–25 days following dextran sulfate sodium treatment. In dynamic contrast-enhanced MRI studies, Gd uptake (K(trans)) and its distribution (v(e)) were measured in muscle and normal and inflamed colons after administering Gd-diethyltriaminepentaacetic acid (Gd-DTPA). T(2)-weighted MR images distinguished normal colon from diffusely thickened colonic wall occurring in colitis (P < 0.0005) and correlated with histologic features. Values of K(trans) and v(e) obtained from dynamic contrast-enhanced MRI were also significantly different in inflamed colons compared to normal colon (P < 0.0005). The results demonstrate that both T(2)-weighted anatomic imaging and quantitative analysis of dynamic contrast-enhanced MRI data can successfully distinguish colitis from normal colon in mice.